2020
DOI: 10.1093/mnras/staa3524
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties and scaling relations of molecular clouds: the impact of star formation

Abstract: Using hydrodynamical simulations of a Milky Way-like galaxy, reaching 4.6 pc resolution, we study how the choice of star formation criteria impacts both galactic and Giant Molecular Clouds (GMC) scales. We find that using a turbulent, self-gravitating star formation criteria leads to an increase in the fraction of gas with densities between 10 and $10^{4}{\, \rm {cm^{-3}}}$ when compared with a simulation using a molecular star formation method, despite both having nearly identical gaseous and stellar morpholo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 83 publications
(108 reference statements)
0
5
0
Order By: Relevance
“…Guszejnov et al (2020) further showed that, in their simulation set, these GMC scaling relationships and distributions of properties exhibited little variation for an isolated galaxy over cosmic time. More recent work has also proposed using variations in the scaling relationships and mass distributions to critically evaluate the star formation models in the star-forming clouds (Fujimoto et al 2019;Grisdale 2021;Li et al 2020) In this work, as well as S18 and Sun et al (2020b), we have identified variations in cloud properties with environment that can be used as additional points of comparison with simulations. In uniformly characterizing GMCs across several galaxies, we find a range of cloud properties and modest changes in the scaling relationships that can give context to any discrepancies between simulations and the canonical cloud population.…”
Section: Evaluating Gmcs In Simulationsmentioning
confidence: 99%
“…Guszejnov et al (2020) further showed that, in their simulation set, these GMC scaling relationships and distributions of properties exhibited little variation for an isolated galaxy over cosmic time. More recent work has also proposed using variations in the scaling relationships and mass distributions to critically evaluate the star formation models in the star-forming clouds (Fujimoto et al 2019;Grisdale 2021;Li et al 2020) In this work, as well as S18 and Sun et al (2020b), we have identified variations in cloud properties with environment that can be used as additional points of comparison with simulations. In uniformly characterizing GMCs across several galaxies, we find a range of cloud properties and modest changes in the scaling relationships that can give context to any discrepancies between simulations and the canonical cloud population.…”
Section: Evaluating Gmcs In Simulationsmentioning
confidence: 99%
“…Simulations of idealized, isolated GMCs tend to find somewhat higher ff , in some cases where feedback is ineffective reaching values as high as in the earlier pre-feedback simulations (Grudić et al 2018), but simulations using initial surface densities, virial parameters, and magnetic field strengths comparable to those of observed GMCs tend to give ff 0.1 (Kim et al 2021b). Simulations of GMCs embedded in full galactic simulations, which capture environmental effects but at the price of lower resolution and heavier reliance on subgrid treatments of feedback, generally give median values of ff ∼ 0.01, albeit with scatters of ∼ 0.5 dex (Semenov et al 2016;Grisdale et al 2019;Grisdale 2021).…”
Section: Cloud Scale Star Formationmentioning
confidence: 99%
“…bursty SFR is expected for the star formation prescription employed in NEWHORIZON (see Grisdale 2021 ). At the time of our analysis ( z = 2) G1 is undergoing a small burst in SFR , we note that despite this burst the galaxy is not a 'starburst' galaxy.…”
Section: G a L A X Y S E L E C T I O N A N D P Ro P E Rt I E Smentioning
confidence: 59%